THE DEVELOPMENT OF PLYOMETRIC BOX EXERCISE MODEL TO INCREASE VOLLEYBALL SPIKER LIMB POWER - Gilang Noviansyah, Dwipa; Iskandar, Dedi; Reva Apriana Sanga Dwi, Dicky (Gladi : Jurnal Ilmu Keolahragaan, 2023)
This research uses development research methodsResearch & Development (R&D) from Borg and Gall. The samples used in this study were 20 members of the volleyball extracurricular activity at SMA NEGERI 1 CIWARU. In this research and development it produces a training modelplyometric box exercise which has been validated, tested and repaired. The results of this research and development are data about valuespretest posttest and a questionnaire using SPSS IBM 25 for windows with a significant level of 0.05. The results of this study indicate that the increaseplyometric box exercise by 5%, namely from the initial test of 77.1% and the final test of 82.00%. From the results of the research that has been done, it can be concluded that with the training modelplyometric box exercise can be developed and applied in the training process. Apart from that with the training modelplyometric box exercise that has been developed, evidence is obtained that there is a significant increase shown in the results of the test data resultspretest, posttest. there is a difference between before and after the training model treatmentplyometric box exercise. Based on these results can be used as a training modelplyometric box exercise as well as being the output product of a training modelplyometric box exercise.